Examining The Impact Of Anxiety And Depression On Sleep Quality Among Healthcare Providers (Journal of Namibian Studies : History Politics Culture, 2024)
Background: Anxiety and depression can significantly impact sleep quality. This can lead to difficulties falling asleep, staying asleep, or experiencing restful sleep. Racing thoughts, worry, and physical symptoms like increased heart rate can make it hard to relax and drift off to sleep, which will affect the quality performance of healthcare providers.Aims: Our objective was to study the influence of anxiety, and depression on sleep quality and to find the factors of sleeping quality to give a recommendation that would reflect well on the healthcare providers’ job satisfaction.Methods: A descriptive cross-sectional design was used utilizing a self-administered questionnaire. Data was collected from healthcare providers using the Zung Self-Rating Depression Scale (SDS). and the Generalized Anxiety Disorder Scale-7. In this study, 350 questionnaires were distributed to qualified respondents, and a total of 190 valid questionnaires (excluded incomplete questionnaires) were returned, indicating a valid response rate of 54%.Results: Statistics showed that more than a quarter of respondents had at least a mild level of depression, which is about 26.9%. Noticed that respondents with sleep disorders (mean = 2.35), and mental disorders (mean = 2.42) showed significantly higher levels of depression as compared to those without the disorder. In addition,  26.4% of respondents had at least a mild level of anxiety. Respondents with sleep disorders (mean = 2.32), and mental disorders (mean = 2.50) showed significantly higher levels of anxiety as compared to those without disorders. There were 13.7% of respondents having mild sleep problems, while 7.9% of respondents having severe sleep problems.Conclusion: Both anxiety and depression can disrupt sleep quality, making it essential to address these mental health conditions to improve overall well-being and sleep patterns.